Volumetric evaluation of maxillary sinuses using CBCTS: radiographic study - Rinaldi, Fabiola; Piattelli, Maurizio; Angiolani, Francesca; Bernardi, Sara; Rastelli, Elena; Varvara, Giuseppe (Italian Journal of Anatomy and Embryology, 2023)
The evaluation of maxillary sinus volumes is fundamental for pre-surgical planning in this area, as well as for the diagnosis of sinusitis and the diagnosis and treatment of maxillary hypoplasia. This study aimed to assess changes in sinus volume over time as a function of different conditions, such as sex, orthodontic treatments like rapid palate expansion, and the presence of edentulism. The Cone-Beam Computed Tomographies of eighteen patients were selected, and their entire sinus volumes were segmented, enabling the measurement of the sinus volume in three spatial dimensions. The collected data were statistically analyzed using the T-Student test and ANOVA. The mean size of the measured right sinus volume was 14.42 cm³, and that of the left sinus was 14.17 cm³. No statistically significant difference was identified between the right and left maxillary sinus volumes, even in correlation with the considered factors (p-value > 0.05). The values found in the present study agreed with those in the literature, confirming the importance of radiographic evaluation of this structure for diagnosis and treatment planning.